Impacts of zero-fare transit policy on health and social determinants: protocol for a natural experiment study - Grimes, Amanda; Berkley-Patton, Jannette; Allsworth, Jenifer E.; Lightner, Joseph S.; Feldman, Keith; Never, Brent; Drees, Betty M.; Saelens, Brian E.; Powell-Wiley, Tiffany M.; Fitzpatrick, Lauren; Bowe Thompson, Carole; Pilla, Madison; et al. (Frontiers in Public Health, 2024)
Population-level efforts are needed to increase levels of physical activity and healthy eating to reduce and manage chronic diseases such as obesity, cardiovascular disease, and type 2 diabetes. Interventions to increase public transit use may be one promising strategy, particularly for low-income communities or populations of color who are disproportionately burdened by health disparities and transportation barriers. This study employs a natural experiment design to evaluate the impacts of a citywide zero-fare transit policy in Kansas City, Missouri, on ridership and health indicators. In Aim 1, comparison to 9 similar cities without zero-fare transit is used to examine differential changes in ridership from 3 years before to 4 years after the adoption of zero-fare. In Aim 2, Kansas City residents are being recruited from a large safety net health system to compare health indicators between zero-fare riders and non- riders. Longitudinal data on BMI, cardiometabolic markers, and economic barriers to health are collected from the electronic health record from 2017-2024. Cross-sectional data on healthy eating and device-measured physical activity are collected from a subsample of participants as part of the study procedures (N=360). Numerous baseline characteristics are collected to account for differences between Kansas City and comparison city bus routes (Aim 1) and between zero-fare riders and non-riders within Kansas City (Aim 2). Evidence on how zero-fare transit shapes population health through mechanisms related to improved economic factors, transportation, physical activity, and healthy eating among low-income groups is expected.